Development of E-Modules Based on Differentiated Learning in IPAS Subjects at SMK - Fitri Yani; Alwen Bentri; Jasrial; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
Education in Vocational High Schools (SMK) faces significant challenges in improving the quality of learning, particularly in Social Sciences (IPAS) subjects that involve abstract concepts, such as Earth and Space. Based on daily test data, only 33.33% of students achieved the Learning Objective Completion Criteria (KKTP), indicating that the majority of students have not yet fully understood the material. This study aims to develop a differentiated learning-based E-Module for the Earth and Space Science material in the IPAS subject at SMKN 8 Padang. The research follows the Research and Development (R&D) method using the Four-D model, consisting of Define, Design, Development, and Disseminate stages. The E-Module was evaluated for validity, practicality, and effectiveness. Results showed that the E-Module achieved high validity, with media receiving 90%, material 81%, and language 100%. The practicality test, conducted with small and large groups, showed scores of 96 and 95%, respectively, while the teachers' evaluation scored 94%. Furthermore, the effectiveness of the E-Module was confirmed with a t-value of 16.293, exceeding the critical value of 2.045, indicating significant improvement in student learning outcomes. The average pretest score was 57.73, which increased to 81.73 after using the E-Module, with a moderate N-Gain score of 57%. These results demonstrate that the E-Module significantly enhances student motivation, understanding, and learning outcomes, making it a viable tool for IPAS instruction in SMK.